2010
DOI: 10.1042/bj20101017
|View full text |Cite
|
Sign up to set email alerts
|

The structure of CYP101D2 unveils a potential path for substrate entry into the active site

Abstract: The cytochrome P450 CYP101D2 from Novosphingobium aromaticivorans DSM12444 is closely related to CYP101D1 from the same bacterium and to P450cam (CYP101A1) from Pseudomonas putida. All three are capable of oxidizing camphor stereoselectively to 5-exo-hydroxycamphor. The crystal structure of CYP101D2 revealed that the likely ferredoxin-binding site on the proximal face is largely positively charged, similar to that of CYP101D1. However, both the native and camphor-soaked forms of CYP101D2 had open conformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Perhaps, the essential features of P450 fold include remote binding sites which can be used for the allosteric regulation of equilibrium and / or kinetic functional properties, such as substrate binding and product dissociation, stability of oxy-complex and autoxidation, as well as fluxes along other uncoupling channels, interactions with redox partners and kinetics of electron and proton transfer steps towards formation of the catalytically active iron-oxygen species. Tentatively, these sites can be suggested to include the progesterone binding site between F’ and G’ helices in CYP3A4, the second camphor binding site proposed between F helix and E helix in CYP101A1 [80] and in CYP101D2 [81], the K + binding site stabilizing B’ helix in CYP101, or residues potentially involved in oligomerization of p450 monomers. Importantly, because of the similar fold of all cytochromes P450, one can expect the appearance of the same homotropic and / or heterotropic interactions as described in well studied CYP3A4, CYP2C8, etc., also in other not as thoroughly known isozymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, the essential features of P450 fold include remote binding sites which can be used for the allosteric regulation of equilibrium and / or kinetic functional properties, such as substrate binding and product dissociation, stability of oxy-complex and autoxidation, as well as fluxes along other uncoupling channels, interactions with redox partners and kinetics of electron and proton transfer steps towards formation of the catalytically active iron-oxygen species. Tentatively, these sites can be suggested to include the progesterone binding site between F’ and G’ helices in CYP3A4, the second camphor binding site proposed between F helix and E helix in CYP101A1 [80] and in CYP101D2 [81], the K + binding site stabilizing B’ helix in CYP101, or residues potentially involved in oligomerization of p450 monomers. Importantly, because of the similar fold of all cytochromes P450, one can expect the appearance of the same homotropic and / or heterotropic interactions as described in well studied CYP3A4, CYP2C8, etc., also in other not as thoroughly known isozymes.…”
Section: Discussionmentioning
confidence: 99%
“…A second binding site for the endogenous substrate camphor was suggested to present in CYP101A1 (P450cam) between F-helix and beta-5 loop [80]. Two alternative sites for camphor binding have been tentatively identified in the open form of the X-ray structure of CYP101D2 [81], one at the substrate access channel, and another on the outside of the molecule near the F-helix, at the similar cavity as in CYP101A1. In CYP3A4 crystallized in the presence of the substrate progesterone, a peripheral binding site for steroid molecule was identified between F’ and G’ helices on the surface of the molecule [82].…”
Section: Cooperativity In P450 Catalytic Cyclementioning
confidence: 99%
“…[20] The access channel is created by movements of the F and G helices and the F/G loop (Figures 2 A, B and S4), and crystal packing interactions could also contribute to the stabilisation of the open conformation ( Figure S2). The mobility of the F/G loop and the surrounding region of CYP enzymes are thought to be important for substrate recognition, entry (7), plus two other minor products 9 % in total.…”
Section: Discussionmentioning
confidence: 99%
“…Both structures have open conformations with an access channel in a similar position to those found in the recently solved structures of CYP101A1 and CYP101D2. [19,20] In common with CYP101D1 and CYP101D2, the proximal face of CYP101C1 has an overall positive electrostatic potential that can interact with a negatively charged area on Arx. [11] However, compared to CYP101D1 and CYP101D2 there CYP101C1 from Novosphingobium aromaticivorans DSM12444 is a homologue of CYP101D1 and CYP101D2 enzymes from the same bacterium and CYP101A1 from Pseudomonas putida.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery and crystallization of other members of the CYP101 family, CYP101D1 [274,275] and CYP101D2 [276], opened additional means to probe the finely tuned and highly efficient mechanism of oxygen activation Both CYP101D1 and CYP101D2 bind camphor in the same orientation as CYP101A1 and catalyze the same hydroxylation with similar high rates (1000-2000 min − 1 ) and almost 100 % efficiency [274,277] Despite the same activity towards the same substrate, there are structural and functional differences between these three isozymes that provide a better understanding of the essential (and not essential) features for optimal P450 catalysis Mutations of the acid-alcohol pair residues D259N and T260A in CYP101D1, analogous to D251N and T252A in CYP101A1, had the same effect: Little or no activity in the Asp/Asn mutant and highly uncoupled NADH consumption in the Thr/Ala mutant in both proteins [274] Critical variations in CYP101D1, as compared to CYP101A1 (where G180 replaces the homologous K178, D182 is used instead of N184 and A366 in CYP101D1 replaces L358 in CYP101A1) may have changed the functional properties with respect to interactions with the redox partner Pdx and/or protonation/substrate binding When these mutants were introduced into CYP101A1 to check for the functional implications of these residues using the native redox partner Pdx [275], the single mutants L358A and K178G had little effect on the activity or structure of CYP101A1 However, the double mutant L358A/K178G had a tenfold slower rate of NADPH consumption than the wild type due to the mostly low-spin state even in the presence of camphor The addition of 400 mM K + converted the double mutant protein to the high-spin form and diminished the difference in steady-state NADPH turnover The crystal structure of the cyanide complex of the mutant CYP101A1 shows the same structural changes as in the wild type, including the key water molecules in the I-helix cleft, indicating that the proton delivery pathway is not perturbed by these mutations [275] Homology analysis revealed that the acid-alcohol pair in the I-helix is a common feature in the great majority of cytochromes P450, although some deviations are evident In the CYP51 class the semi-conserved acid side-chain (D251 in CY-P101A1) is replaced by a histidine [278] In the rat CYP51 enzyme, the mutation H314D resulted in a sevenfold lower 14-demethylase activity [279] In some cytochromes P450 the alcohol side-chain from threonine or serine is replaced by alanine, as in P450eryF (CYP107A1) and CYP158A2 Based on the X-ray structural studies of these two enzymes, the concept of substrate-assisted catalysis was proposed as an alternative to the missing side-chain of Thr/Ser [80,280] The functionally important water molecules forming the proton delivery pathway are stabilized at the proper position close to the coordinated dioxygen by hydrogen bonding to the substrate hydroxyl group instead of the alcohol side-chain [73,80,…”
Section: Bleed Points Of Inefficiencymentioning
confidence: 99%